The effect of trapping on the migration and survival of Atlantic salmon smolts - Sortland, Lene Klubben; Jepsen, Niels; Kennedy, Richard; Koed, Anders; del Villar-Guerra, Diego; Lennox, Robert J.; Birnie-Gauvin, Kim; Aarestrup, Kim (River Research and Applications, 2024)
Publication history: Accepted - 26 June 2024; Published online - 15 July 2024. Electronic tags are often used to track the freshwater-marine migrations of smolts, where smolts are captured for tagging pre-migration (e.g., via electrofishing) or during-migration (e.g., via traps). Pre-migration capture allows smolts to initiate and complete their downstream migration unhindered, but risks smolt loss before the migration commences. The contrary is the case for during-migration trap-caught smolts, but trapping smolts temporarily halts their seaward journey which may negatively impact their progress. This study investigated the effect of trapping on the behaviour and survival of migrating Atlantic salmon (Salmo Salar) smolts using acoustic telemetry. We compared the movements and survival of smolts tagged before the smolt run captured by electrofishing (“comparator”) with smolts trapped and tagged during the smolt run (“trapped”). A total of 478 smolts were tagged and released in River Skjern (2020 and 2022), Denmark, and 82 smolts in River Ballycastle (2022), Northern Ireland, and their seaward movements were monitored using acoustic receivers deployed in the river, fjord, and coastal area. In River Skjern in 2022, comparator smolts migrated earlier than trapped smolts, likely because these constituted more of the larger-sized, earlier migrating individuals. We found no differences in descent trajectories, diel patterns, progression rates, or survival between trapped smolts and comparator smolts in any of the rivers or study years. Thus, our results support the use of during-migration trapping as a low-impact method to capture smolts for telemetry studies, with trapped samples (if held <24 h) yielding comparable results in terms of behaviour and survival with non-delayed pre-migration tagged fish. NASCO project (SMOLTRACK IV); Danish Net and Fishing License